Anticancer Evaluation of Novel Benzofuran–Indole Hybrids as Epidermal Growth Factor Receptor Inhibitors against Non-Small-Cell Lung Cancer Cells - Yechan Lee; Sunhee Lee; Younho Lee; Doona Song; So-Hyeon Park; Jieun Kim; Wan Namkung; Ikyon Kim (Pharmaceuticals, 2024)
The epidermal growth factor receptor (EGFR), also known as ErbB1 and HER1, belongs to the receptor tyrosine kinase family. EGFR serves as the primary driver in non-small-cell lung cancer (NSCLC) and is a promising therapeutic target for NSCLC. In this study, we synthesized a novel chemical library based on a benzofuran–indole hybrid scaffold and identified 8aa as a potent and selective EGFR inhibitor. Interestingly, 8aa not only showed selective anticancer effects against NSCLC cell lines, PC9, and A549, but it also showed significant inhibitory effects against the double mutant L858R/T790M EGFR, which frequently occurs in NSCLC. In addition, in PC9 and A549 cells, 8aa potently blocked the EGFR signaling pathway, cell viability, and cell migration. These findings suggest that 8aa, a benzofuran–indole hybrid derivative, is a novel EGFR inhibitor that may be a potential candidate for the treatment of NSCLC patients with EGFR mutations.